Examining the Problems Faced by Students with Special Needs in the Distance Education Process during the COVID-19 Pandemic - Nilüfer Yüksel; Ceren Çoban; Dila Nur Yazıcı (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - In this study, we examined the problems faced by students with special needs in the distance education process in Turkey from the perspectives of their parents and teachers. Materials/methods - We used case study in this research. Our study group consisted of seven parent-teacher pairs. We used a demographic information form and standardized interview forms. Our analysis technique was content analysis. Results - From the standardized interviews, it was determined that the developmental problems observed by parents and teachers in children were in the areas of academic, socioemotional, and language development. In contrast, instructional problems were generally related to class participation. Conclusion - As a result of the research, we have seen that children with special needs face problems in their academic, social skills, and language development. It was determined that inclusive students experienced difficulties in their usage of technology, participating in online classes, and maintaining their attention.